2016
DOI: 10.1210/jc.2015-2802
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Glucose Sensitivity Is Linked to Insulin/Glucagon Bihormonal Cells in Nondiabetic Humans

Abstract: Our data suggest that poor β-cell glucose sensitivity is linked to islet transdifferentiation, possibly from α cells to β cells, in an attempt to cope with higher demands for insulin secretion. Understanding the mechanism(s) that underlies the adaptive response of the islet cells to insulin resistance is a potential approach to design tools to enhance functional β-cell mass for diabetes therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…In particular, it has been demonstrated that under conditions of severe pancreatic injury including a near‐total beta‐cell ablation, bi‐hormonal cells expressing both insulin and glucagon can be observed in the pancreas . Very recently, it has been also reported that in the human pancreas, poor beta‐cell glucose sensitivity could be linked to the number of alpha‐beta double + islet cells . In this regard, it may be worth to mention that in our samples, bi‐hormonal cells were preferentially located at the periphery of islets (ie, in close connection with the cells of the surrounding inflammatory infiltrate) and are characterized by a higher percent of beta than alpha granules (beta granules: 68% ± 4.4%; alpha granules: 32% ± 4.4%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In particular, it has been demonstrated that under conditions of severe pancreatic injury including a near‐total beta‐cell ablation, bi‐hormonal cells expressing both insulin and glucagon can be observed in the pancreas . Very recently, it has been also reported that in the human pancreas, poor beta‐cell glucose sensitivity could be linked to the number of alpha‐beta double + islet cells . In this regard, it may be worth to mention that in our samples, bi‐hormonal cells were preferentially located at the periphery of islets (ie, in close connection with the cells of the surrounding inflammatory infiltrate) and are characterized by a higher percent of beta than alpha granules (beta granules: 68% ± 4.4%; alpha granules: 32% ± 4.4%).…”
Section: Discussionmentioning
confidence: 56%
“…27 Very recently, it has been also reported that in the human pancreas, poor beta-cell glucose sensitivity could be linked to the number of alpha-beta double + islet cells. 28 In this regard, it may be worth to mention that in our samples, bi-hormonal cells were preferentially located at the periphery of islets (ie, in close connection with the cells of the surrounding inflammatory infiltrate) and are characterized by a higher percent of beta than alpha granules (beta granules: 68% AE 4.4%; alpha granules: 32% AE 4.4%). Although the mechanisms responsible for the formation of bi-hormonal cells are still to be elucidated, it might be attractive to speculate that the hostile environment due to autoimmunity in T1D could contribute to a partial transformation of more vulnerable beta cells towards a more resistant alpha-like phenotype.…”
Section: Discussionmentioning
confidence: 71%
“…The percentage of bihormonal cells was higher inside larger islets, thus suggesting that α‐to‐β conversion could be an adaptive response to insulin resistance. The increase in glucagon+/insulin + and insulin+/CK19+ co‐expressing cells only partially explains the observed increase in the β‐cell mass; it could be that most converting α‐ and ductal cells lose glucagon and CK19 expression, respectively, thus implying that the extent of reprogramming would be higher than that observed, but underestimated because of the lack of lineage tracing tools in humans . The same group suggested that poor β‐cell glucose sensitivity in obesity would lead to islet cell type interconversion, possibly α‐to‐β, as an attempt to cope with a higher insulin secretion demand …”
Section: Physiological Stressmentioning
confidence: 96%
“…Although these findings were challenged [58,59], oral GABA/probiotic supplementations were shown to improve beta-cell function and eliminate insulin medication in a case report of a T2DM patient indicating some beneficial effects of the GABA signalling pathway that will require further investigation [60,61]. Independently, alpha-to-beta-cell conversion opens new T1DM therapeutic opportunities as bi-hormonal cells expressing both insulin and glucagon were detected in non-diabetic insulin-resistant individuals as well as patients with T1DM pinpointing to an important role of such process in humans [62,63]. Substantiating this premise was the recent demonstration that human alpha-cells can convert to functional beta-cells [64].…”
Section: Beta-cell Regeneration Therapiesmentioning
confidence: 99%